Analysis of the Performance in the Process of Solar Still using Textile Wastewater. (June 2019) - Chávez, S; Terres, H; Lizardi, A; López, R; Monzalve, R
Abstract: In this work an analysis is realized on the performance of a solar distiller using textile wastewater from fiber dyeing processes. A solar still with shed was used, where 6 experimental tests were performed using Black B5, Blue 198 and Red 81, with and without auxiliary, for each test. Temperatures were measured on the cover of glass, container absorbent, fluid and environment. The incident solar radiation was obtained by means of modules ADAM and a pyranometer. The processing of the acquired information was done by means of the software LabVieW. An energy balance was established and the Dunkle's thermal model was used to evaluate the thermal behavior of the solar distillation. The following values were o maximum values of 37.4 %, 25 % and 21.4 % for Black B5, Blue 198 and Red 81 without auxiliary respectively and 45.4 %, 34 % and 26.7 % for Black B5, Blue 198 and Red 81 with auxiliary respectively, in such a way that the efficiency increases when the textile wastewater contained auxiliary.